2021
DOI: 10.5713/ab.21.0139
|View full text |Cite
|
Sign up to set email alerts
|

Sequential use of real-time polymerase chain reaction and enzyme-linked immunosorbent assay techniques verifies adulteration of fermented sausages with chicken meat

Abstract: Objective: Detection of adulteration in processed meats is an important issue for some countries due to substitution of beef with a cheaper source of protein like poultry. In this study, the presence of chicken meat was investigated using real-time polymerase chain reaction (Real-time PCR) and enzyme-linked immunosorbent assay (ELISA) techniques to verify adulteration of fermented sausage samples.Methods: A total of 60 commercial samples were collected from 20 establishments in three replicates including 10 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…None of the treatments had a significant effect on the moisture contents of sucuks during production, indicating that the addition of bay leaf extracts produced similar moisture contents to the control and AA groups. The previous studies (Benli & Barutcu, 2021 ; Con & Gökalp, 1998 ; Siriken et al., 2009 ) indicated that sucuk samples collected from the different regions in Turkey had highly variable moisture contents (20.96%–50.49%). Nonetheless, in this study, variation of the moisture contents in sucuk samples was in the expected ranges for manufacturing a traditional fermented sucuk (moisture content of <40%) even after the incorporation of bay leaf extracts when compared to the control and AA groups, which indicated a lack of standardized manufacturing methods for sucuks in the Turkish market.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…None of the treatments had a significant effect on the moisture contents of sucuks during production, indicating that the addition of bay leaf extracts produced similar moisture contents to the control and AA groups. The previous studies (Benli & Barutcu, 2021 ; Con & Gökalp, 1998 ; Siriken et al., 2009 ) indicated that sucuk samples collected from the different regions in Turkey had highly variable moisture contents (20.96%–50.49%). Nonetheless, in this study, variation of the moisture contents in sucuk samples was in the expected ranges for manufacturing a traditional fermented sucuk (moisture content of <40%) even after the incorporation of bay leaf extracts when compared to the control and AA groups, which indicated a lack of standardized manufacturing methods for sucuks in the Turkish market.…”
Section: Resultsmentioning
confidence: 97%
“…The hardness of the sausage begins to rise at a pH of 5.4 and continues to rise progressively until the pH drops to 4.9. Although most of the studies in the literature indicated a high level of variability among the pH values (4.53–6.74) of sucuk samples collected from the Turkish market (Benli, 2017 ; Benli & Barutcu, 2021 ; Erkmen & Bozkurt, 2004 ; Gençcelep et al., 2008 ), in this study, pH decreases were in the expected ranges for manufacturing a traditional fermented sucuk, and the incorporation of bay leaf extract produced similar pH values when compared to control and AA samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the amplification capacity of nucleic acids can improve the detection sensitivity of corresponding DNA analytical methods. Commonly used nucleic acid-based detection methods include polymerase chain reaction (PCR) [ 13 ], real-time fluorescent PCR [ 14 ], digital PCR [ 15 ], multiplex PCR [ 16 ], loop-mediated isothermal amplification (LAMP) [ 17 ], cross-priming amplification (CPA) [ 18 ], and recombinase polymerase amplification (RPA) [ 19 , 20 ]. PCR is considered the “gold standard” for identifying adulterated meat products and has been successfully employed to identify beef, lamb, pork, and chicken [ 21 ].…”
Section: Introductionmentioning
confidence: 99%